2010
DOI: 10.1016/j.jcrs.2009.12.048
|View full text |Cite
|
Sign up to set email alerts
|

Straylight measurements in pseudophakic eyes with natural and dilated pupils: One-year follow-up

Abstract: Straylight decreased significantly in the first year after cataract surgery. Furthermore, it increased with increasing pupil size, which was associated with a capsulorhexis smaller than the pupil. This indicates the capsulorhexis should be as large as possible to prevent straylight, especially under low-luminance conditions when the pupil is large.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
0
7
1
Order By: Relevance
“…Cerviño et al also found that straylight values were not associated with the pupil size of the subject [19]. However, van Gaalen et al reported that straylight increased with increasing pupil size in pseudophakic eyes at one year after surgery [20]. Straylight values were significantly higher in dilated than those in natural pupils, which was contradictory to our study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Cerviño et al also found that straylight values were not associated with the pupil size of the subject [19]. However, van Gaalen et al reported that straylight increased with increasing pupil size in pseudophakic eyes at one year after surgery [20]. Straylight values were significantly higher in dilated than those in natural pupils, which was contradictory to our study.…”
Section: Discussioncontrasting
confidence: 99%
“…In van Gaalen's study, the presence of the anterior capsule rim in the pupillary area, not the pupil size, was considered as the main reason for the increase in straylight. The opacity of the anterior capsule rim may have increased the straylight significantly [20]. van Gaalen measured straylight using natural pupils and dilated pupils at one year after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for the high straylight numbers in the study by Guo et al 34 might be that the straylight measurements were performed in a dark room with a subsequently large pupil diameter. Van der Meulen et al 24 and van Gaalen et al 35 separately found that intraocular scatter is closely related to pupil diameter in pseudophakic eyes. Their findings show that 1.0 mm of visible capsulorhexis remnant induces 0.52 log units of additional straylight.…”
Section: Discussionmentioning
confidence: 99%
“…The pupils were undilated because dilation increases straylight. 25,26 The straylight source in the C-Quant Straylight Meter is an annulus with a 5 to 10 radius in the visual field that corresponds to the areas of guttae that we measured. 27 Unreliable straylight measurements were detected by the reliability parameters, and data with low reliability parameters were excluded.…”
Section: Methodsmentioning
confidence: 99%